2021
DOI: 10.1016/j.jclinepi.2021.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials in COVID-19 management & prevention: A meta-epidemiological study examining methodological quality

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 135 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…Prior studies have examined the COVID-19 trial landscape, evaluating trial design quality [24,25], choice of outcome [26], and presenting descriptive statistics on COVID-19 trials characteristics [2,5,6,[8][9][10][11]. This is the first study to assess the prevalence of informative COVID-19 clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have examined the COVID-19 trial landscape, evaluating trial design quality [24,25], choice of outcome [26], and presenting descriptive statistics on COVID-19 trials characteristics [2,5,6,[8][9][10][11]. This is the first study to assess the prevalence of informative COVID-19 clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…We note that these attributes should not be interpreted as indicators of the rigor of the trials or the efficacy of the interventions being examined. Any appraisal of adherence to reporting guidelines (see Quinn et al, 2021) or evaluation of the strength of evidence (see Honarmand et al, 2021) for any of the individual studies in our sample or in the literature as a whole was beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…We describe the fragility index by subgroups of trial characteristics in Table 2. The median (IQR) fragility indexes of RCTs in treatment drugs was 2.5 (1-6); in others it was 4.5 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In contrast, the median (IQR) fragility index of vaccine trials was 119 (61-139).…”
Section: The Fragility Index In Covid-19 Trialsmentioning
confidence: 99%
“…and S.S.) screened the titles and abstracts of all identified articles in accordance with the following prespecified eligibility criteria. The inclusion criteria were RCTs that (1) were superiority trials, (2) randomly assigned patients 1:1 into 2 parallel groups, (3) reported at least 1 dichotomous or time-toevent outcome as statistically significant in the abstract, and (4) tested an intervention for COVID-19.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation